Relevansi Dimensi Spiritual Manusia Terhadap Implementasi Pendidikan Karakter - Haryanto, Sri (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This study aims to explore the relevance of the spiritual dimension of humans to the implementation of character education. Through a qualitative approach, this study analyzes spiritual concepts in various religions and philosophies and relates them to educational values. This study used a descriptive qualitative research method. A research approach that aims to describe and understand phenomena that occur in their natural context. This research does not focus on hypothesis testing or statistical generalizations but rather emphasizes a deep understanding of a problem or phenomenon. Researchers use an inductive approach to identify patterns, themes, and characteristics that emerge from the collected data. The results of descriptive qualitative research are in-depth descriptions of the phenomena studied, which can provide rich and contextual understanding. Based on research, it was found that the spiritual dimension of humans and character education are closely related. Character education aims to form good and quality character in individuals, while the spiritual dimension involves understanding and awareness of the nature of self, life, and its creator. The contribution of the spiritual dimension of humans in character education can provide a strong foundation for the formation of individuals with integrity, responsibility, and care for others. The implication of this research is the need to include a spiritual approach in the character education curriculum as an effort to form a generation that has a strong morality and positive attitude towards life.